PENGGUNAAN PERMAINAN PUZZLE DALAM PEMBELAJARAN MATA DIKLAT WHOLE OF GOVERNMENT BAGI PESERTA PELATIHAN DASAR CALON PEGAWAI NEGERI SIPIL - Zaniar Aswandi (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2020)
Delivering training subjects by using game may creates fun situation which will bring positive impact to learner’s motivation of studying. This research tried to answer a problem question whether the using of puzzle game will make a difference in the result of study between experiment group and control group in the delivery of training subject Whole of Government. This is a quasi experiment research with quantitative approach by using the tool of SPSS application. There are two populations as subjects of the research, coming from 2 classes of Basic Training for Probationary Civil Servant (Latsar CPNS) organized in the Agency of Human Resources Development of West Kalimantan Province. Data are gained by using pretest and posttest to samples which are classified as experiment class and control class. Data analysis is conducted through several tests, they are: validity test, reliability test, normality test and test for comparative hypothesis. The result of hypothesis test by using t-test for independent samples accepts null hypothesis meaning that there is no sigificant difference in the result of study delivery between experiment class and control class.